Perancangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web pada SMA Islam Terpadu Darul Amilin Kabupaten Aceh Selatan - Harwalis (Design Journal, 2024)
The advancement of information technology has had a significant impact on various sectors, including education. One of the innovations in education is the development of a web-based student admission information system. SMA Islam Terpadu Darul Amilin in South Aceh Regency still relies on manual processes for student enrollment, causing inefficiencies and inaccuracies in data management. This study aims to design and implement a web-based admission information system to simplify the registration process for prospective students and parents, as well as to expedite administrative reporting. The research utilizes the waterfall software development model, with UML employed for system design. PHP programming language and MySQL are used as the foundation of the system. This system is expected to provide fast and accurate information, reducing errors in the administration of new student admissions.